TERAPI BERMAIN KOLASE CARTOON TERHADAP TINGKAT KOOPERATIF ANAK PRASEKOLAH - Ayu Ainun Asma UL Husna Miftahul Janah; Ria Setia Sari; Febi Ratnasari (Nusantara Hasana Berdikari, 2021)
Collage is a technique of sticking various elements into one frame, so the newest artwork is produced. One of interventions for reducing stress and uncooperative of preschool students are the therapy of cartoon collage playing, because the use of cartoon collage can be useful to enhance the students to identify various colors, develop their fine motoric skill and improve their self-confidence. The objective of the research to find out the influence of the therapy of cartoon collage playing as a method to improve the cooperative levels of preschool students. The research method: Literature review is used as the research method. The analysis of 20 related journals, it can be concluded that the therapy of cartoon collage playing is beneficial to improve the cooperative levels of preschool students and the results from synthetic matrix can be divided into three components, namely: input, process, and output.